Molecular Characteristics of Lopang (Gymnopetalum cochinchinense) Originating from Riau Based on matK and trnL-trnF Intergenic Spacer - Herman, Herman; Akmal, Fidia; Nurbaiti, Nurbaiti; Siahaan, Citra Winarni; Lestari, Wahyu; Adiwirman, Adiwirman; Altuhaish, Adeel Abdulkarim Fadhl; Roslim, Dewi Indriyani (Biosaintifika: Journal of Biology & Biology Education, 2025)
Lopang (Gymnopetalum cochinchinense) is a herbaceous plant traditionally consumed as a vegetable by communities in Riau Province, Indonesia. However, DNA barcode sequence data for this species remain limited. These findings underscore the importance of analyzing DNA barcode sequences of matK and trnL-trnF intergenic spacer (IGS) lopang from Riau. This study highlights the analysis of DNA barcode sequences matK and trnl-trnf intergenic spacer (IGS) in lopang from Riau province. This study applies sampling, DNA extraction, Polymerase Chain Reaction (PCR), electrophoresis, sequencing, and bioinformatics data analysis using BioEdit 7, BLASTn (Basic Local Alignment Search Tool) to find sequence similarities with the GenBank database, Management and analyzed DNA sequences with MESQUITE, Multiple alignments using ClustalW and MEGA11 to create dendrograms. Fresh leaves were collected from Rokan Hulu Regency in Riau Province. The results showed that matK and trnL-trnF IGS DNA sequences of lopang measured 752 bp and 410 bp, respectively. BLASTn analysis revealed that lopang has 99.73% similarity with G. chinense based on the matK sequence and 99.76% similarity based on the trnL-trnF IGS sequence. The analysis revealed a variation of 13 nucleotides, 1 critical nucleotide and no indels in the matK sequence, while in the trnL-trnF IGS sequence there were 19 nucleotide variations, 1 critical nucleotides and 5 indels. As a final point, lopang from Riau is closely related to G. chinense. The findings of this research contribute to the molecular identification of this species and benefit science, such as providing an understanding of plant evolution, species identification, genetic analysis, and the development of molecular markers in the Cucurbitaceae family.